A Study of Nestlé Financial Analysis - Gooy, Shiau Yen; Gong, Pui San; Gong, Why Kim; Han, Rui; Rana, Vanshika (AIBPM Publisher, 2023)
Nestlé is a well-known food and beverage corporation in Malaysia and worldwide. The vision of the Nestlé company is to provide 'Good Food, Good Life to the consumers. 'Good Food, Good Life' displays the promise they commit themselves to every day, everywhere as the leading Nutrition, Health, and Wellness Company globally. The purpose of this study is to analyze the financial performance of Nestlé within five consecutive years, which is from 2016 to 2020. Financial performance must be compared to track their progress in terms of stability, liquidity, profitability, and market share retention. To compare financial performance, quantitative data from the annual report were required. Market value ratios, profitability ratios, efficiency ratios, and liquidity ratios are used to analyze a company's financial performance. Our paper provides information on the ratios that revealed the company's financial performance. This paper can be used as a guide that highlights an overview of the company's financial health, allowing investors and stakeholders to make informed investment decisions.